Production and Characterization of Wild Sugarcane (Saccharum spontaneum L.) Biochar for Atrazine Adsorption in Aqueous Media - Josué Prens; Zohre Kurt; Arthur M. James Rivas; Jorge Chen (Agronomy, 2022)
Wild sugarcane (Saccharum spontaneum L.) is an invasive plant species in the Central American region. Due to its low nutrient and water requirements, it can grow fast and displace native species. Therefore, its biomass is considered a waste to prevent the further distribution of the specie. This study investigates the production and characterization of wild sugarcane biochar to provide a use for its waste. The produced biochar was used for atrazine adsorption in aqueous solutions to provide a possible application of this biochar near the water bodies that were often detected to be contaminated with atrazine. The biochar was produced via top-lit updraft gasification with airflow rates between 8 to 20 L/min, achieving yields ranging from 22.9 to 27.5%. Batch experiments revealed that biochar made at 12 L/min presented the best removal efficiency (37.71–100%) and the maximum adsorption capacity (qm = 0.42 mg/g). Langmuir (R2 = 0.94–0.96) and Freundlich (R2 = 0.89–0.97) described the experimental data appropriately. Fourier transform infrared spectroscopy suggested that atrazine removal in wild sugarcane biochar could be mainly due to carboxylic functional groups. In addition, the biochar organic carbon composition contributed to a higher removal capacity in biochar produced at different airflow rates.